KESALAHAN BERBAHASA PADA SURAT DINAS SMA NEGERI 9 KOTA JAMBI - Firman Tara; Desri Karlinda (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research aims at describing language errors in writing letter numbers, mailing letter, opening paragraph, and closing paragraph of official letters of SMA Negeri 9 Jambi City year of  2019. This research is a qualitative descriptive. The technique used in collecting data are observation and documentation. The results of the analysis show that the errors in writing letter numbers are the use of colons and slashes which are preceded and followed by a space. Errors in writing mailing letter is indicated in the use of kepada which indicates language redundancy; the use of a colon (:) which should be replaced by a period (.); the use of punctuation marks (.) at the end of the mailing address; and the use of bold letters in the mailing address. Written errors in the opening paragraph of the letter are the writing of the opening greeting Dengan hormat in the beginning of the paragraph that should be included in the first sentence of the letter opening. Written errors in the closing paragraphs of letters are the incomplete closing sentences of the letter which should have been mentioned earlier, written behind the word demikianlah; and errors in the use of preposition di.